Insights into the stereoselectivity of human SETD7 methyltransferase. Issue 16 (21st March 2019) - Tang, Bowen; Li, Baicun; Li, Boqun; Qin, Jingbo; Zhao, Junming; Xu, Jianwenn; Qiu, Yingkun; Wu, Zhen; Fang, Meijuan
Abstract : This work clearly reveals the interaction of SAM/hSET7/( R / S )-PFI-2 systems, and confirms that the different bioactive energy barriers of ( R )-PFI-2 and ( S )-PFI-2 lead to the tremendously different inhibitory activities between these two antipodes. Abstract : Human SETD7 methyltransferase (hSETD7) is involved in a wide range of physiological processes, and has been considered as a significant target to develop new drugs. ( R )-PFI-2, one hSETD7 inhibitor, could bind to the pocket of substrates with potent (low nanomolar) activity and high selectivity, while its enantiomer ( S )-PFI-2 showed 500-fold less activity in IC50 determination. Why do this pair of enantiomers, with nearly identical structures, exert tremendously different inhibitory activity? We performed a total of 900 ns long-timescale molecular dynamics (MD) simulations and 80 ps hybrid quantum mechanics/molecular mechanics (QM/MM) MD simulations to understand the molecular mechanism of the stereoselectivity of hSETD7. For each SAM/hSETD7/PFI-2 system, we characterized and compared the residual fluctuation of hSETD7, and generated molecular interaction fingerprints (IFP) to exemplify the propensities of SAM/hSETD7-inhibitor interactions. Based on the QM/MM MD, we accurately captured the difference of hydrogen bonds between the SAM/hSETD7/( R )-PFI-2 and SAM/hSETD7/( S )-PFI-2 systems. Especially the strength of the hydrogen bond between G336 and two inhibitors, which determines the stability of the post-SET loop. The energy barrier for ( S )-PFI-2 was much bigger than ( R )-PFI-2 from global minimum to bioactive conformation as the potential energy surface scanning (PES) showed. Moreover, by estimating the binding affinity and phylogenetic tree analysis, we discovered 16 hotspots were essential for binding both enantiomers but the specific mode of interaction between these hotspots and enantiomorphs is different. Our findings reveal the effect of chirality on the inhibition activity of hSETD7 in detail, and provide valuable information for hSETD7 structure-based drug development.